Remembering and fictionalizing inhospitable Europe: The experience of Portuguese retornados in Dulce Maria Cardoso’s The Return and Isabela Figueiredo’s Notebook of Colonial Memories - Mendes, Ana Cristina (2017)
At a time when issues of migration, both voluntary and forced, are rife, it is vital to further unpack the politics and poetics of hospitality as a complex discourse of inclusion and exclusion, belonging and alienation, welcoming and rejection. Situated within the framework of Derridean thought on hospitality, this article examines Dulce Maria Cardoso’s O Retorno (The return, 2011) and Isabela Figueiredo’s Caderno de Memórias Coloniais (Notebook of colonial memories, 2009) with a focus on the return to the metropolitan centre or Metrópole – actually “repatriation” from former Portuguese African colonies to Portugal – and the subsequent estrangement and negotiation of inhospitality and hostility experienced by Cardoso’s and Figueiredo’s characters. If travel and migration in themselves present an identitary challenge, in the sense that the encounter with the other coincides with the reconfiguration of self, the issues of gender and a forced return “home” add complexity to this challenge. This article makes a case for the intersection of world-systems theory and Portuguese (de)colonization. The identitary intersections and overlaps the retornado characters experience in The Return and Notebook of Colonial Memories are further compounded by the fact that their authors speak from the south within the north, giving voice to the interidentity of the Portuguese as what Sousa Santos has termed “Calibanized Prospero” and “Prosperized Caliban”.